2023
DOI: 10.1002/cpt.2907
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Metabolism of Diclofenac by Polymorphic UGT2B17 Correlates with its Highly Variable Pharmacokinetics and Safety across Populations

Abstract: Although the United States and Europe have shifted to the prescription use of oral diclofenac due to several serious incidences of cardiotoxicity, it is one of the most commonly used over-the-counter (OTC) pain medicines in major parts of the world. We elucidated the quantitative and tissue-specific contribution of uridine diphosphateglucuronosyltransferases 17 (UGT2B17) in diclofenac metabolism and pharmacokinetics (PK). UGT2B17 is one of most deleted genes in humans with the gene deletion frequency ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…However, UGT2B17 is highly polymorphic resulting in different expression levels of the encoded protein, 45 which can also be seen in the striking protein levels variability in the liver (CV, 162.6%) and jejunum (CV, 96.7%) as observed in our study. A very recent study has reported that the UGT2B17‐mediated intestinal metabolism of diclofenac correlates with its highly variable pharmacokinetics and safety 46 . Moreover, this genetic variability was discussed to be associated with various types of cancer, that is, genetic UGT2B17‐deletion was identified as risk factor for head, neck, and esophageal cancer, whereas it seems not to be associated with testosterone dependent tumors, such as prostate cancer 47,48 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, UGT2B17 is highly polymorphic resulting in different expression levels of the encoded protein, 45 which can also be seen in the striking protein levels variability in the liver (CV, 162.6%) and jejunum (CV, 96.7%) as observed in our study. A very recent study has reported that the UGT2B17‐mediated intestinal metabolism of diclofenac correlates with its highly variable pharmacokinetics and safety 46 . Moreover, this genetic variability was discussed to be associated with various types of cancer, that is, genetic UGT2B17‐deletion was identified as risk factor for head, neck, and esophageal cancer, whereas it seems not to be associated with testosterone dependent tumors, such as prostate cancer 47,48 …”
Section: Discussionmentioning
confidence: 99%
“…A very recent study has reported that the UGT2B17mediated intestinal metabolism of diclofenac correlates with its highly variable pharmacokinetics and safety. 46 Moreover, this genetic variability was discussed to be associated with various types of cancer, that is, genetic UGT2B17-deletion was identified as risk factor for head, neck, and esophageal cancer, whereas it seems not to be associated with testosterone dependent tumors, such as prostate cancer. 47,48 With respect to CES, which were shown to be the most abundant of all investigated enzymes in the human intestine and liver, CES1 was significantly higher expressed on gene and protein levels in the liver than in the jejunum, whereas it was the opposite for CES2.…”
Section: Articlementioning
confidence: 99%
“…Considering the cardiotoxicity risk of diclofenac, proteomics-informed PBPK modeling suggests that the diclofenac dose should be decreased in women and the carriers of UGT2B17 gene deletion. 18 Similarly, quantitative proteomics is useful in the discovery and quantification of efficacy biomarkers. For example, warfarin is a narrow therapeutic index drug that requires stratification of subjects based on the levels of descarboxylated prothrombin.…”
Section: Quantitative Proteomics In Translational Pharmacology (B Pra...mentioning
confidence: 99%
“…UGT2B17 gene deletion carriers and women are vulnerable to slower metabolism and increased bioavailability of diclofenac. Considering the cardiotoxicity risk of diclofenac, proteomics‐informed PBPK modeling suggests that the diclofenac dose should be decreased in women and the carriers of UGT2B17 gene deletion 18 . Similarly, quantitative proteomics is useful in the discovery and quantification of efficacy biomarkers.…”
Section: Introductionmentioning
confidence: 99%